Does colour matter? Genetic differentiation of colour morphs of the Asian golden web spider Nephila antipodiana (Araneae: Nephilidae) - Low, Van Lun; Norma-Rashid, Yusoff; Ubaidillah, Rosichon; Yusoff, Amri; Prakash, Batah Kunalan; Tan, Tiong Kai; Chen, Chee Dhang; Sofian-Azirun, Mohd (Brill Academic Publishers, 2018)
Here we present the first attempt to test for genetic differentiation among four distinct colour morphs of the Asian golden web spider Nephila antipodiana Walckenaer. Fragments of the 18S rRNA (18S) and cytochrome c oxidase subunit I (COI) genes were sequenced in eight populations of N. antipodiana belonging to four distinct colour morphs: Yellow, yellowish green, and two newly discovered morphs, reddish yellow and white-spotted. The nuclear sequences amplified from females of the four colour morphs were identical. The mitochondrial COI sequences, on the other hand, revealed slightly higher variation by recovering three haplotypes belonging to two different clades. Clade I comprises yellow, yellowish green and reddish yellow morphs from the mainland of Southeast Asia and Java, whereas clade II is restricted to white-spotted morph originating from Borneo. The low genetic divergence between both clades, despite being distinctive, undoubtedly provides new insight into the genetic diversity of this polymorphic species.